Ngereng Dhebu: Tinjauan Konstruksi Sosial-Edukatif Di Lingkungan Alumni Pesantren Madura - Syarifuddin, Muhammad; M. Mansyur (LPPM IAIN Sorong, 2024)
This research aims to determine the moments of internalization, objectification and externalization in forming the Ngereng Dhebu Culture for the Association of Alumni and Sympathizers (IKBASS) of the Miftahul Ulum Pannyeppen Pamekasan Islamic Boarding School. The approach used is qualitative with a case study type at the Miftahul Ulum Pamekasan Islamic boarding school. The data collection techniques used were interviews and observation with the data analysis technique being an interactive model. The results of this research show that the internalization of Ngereng Dhebu Culture for alumni at the Miftahul Ulum Panyeppen Pamekasan Islamic Boarding School is carried out with three main processes, namely acceptance, appreciation and practice. This moment is implemented through educational, learning and teaching activities. The moment of objectification in forming the